Duration of drug holiday of oral bisphosphonate and osteoclast morphology in osteoporosis patients with medication-related osteonecrosis of the jaw. Issue 4 (July 2022) - Morishita, Kota; Otsuru, Mitsunobu; Soutome, Sakiko; Hayashida, Saki; Murata, Maho; Nakamura, Wataru; Umeda, Masahiro
Abstract: Objective: Medication-related osteonecrosis of the jaw often occurs after tooth extraction; therefore, the withdrawal of antiresorptive agents for 2–3 months before invasive dental procedures is recommended, despite the lack of evidence on its effectiveness. We aimed to histologically investigate the relationship between the drug holiday of oral bisphosphonate and morphological recovery of osteoclasts. Methods: Thirty osteoporosis patients (26 women and 4 men; average age, 82.5 years) with a history of bisphosphonate administration, medication-related osteonecrosis of the jaw, and surgery were included. Bisphosphonates were withdrawn for 0–3 months in 23 patients, 3–6 months in three, and> 6 months in four. Absence of cathepsin-K positive osteoclasts or release of only huge multinucleated cells on the bone surface on histological examination of the surgical specimens was judged as osteoclast suppression. Results: Normal osteoclast morphology was observed in only four patients. Osteoclasts remained suppressed in 21/23 patients (91.3%) with a drug holiday< 3 months, 2 of 3 patients (66.7%) with a 3–6-month drug holiday, and 3 of 4 patients (75%) with>than 6 month-drug holiday. Conclusion: In osteoporosis patients receiving oral bisphosphonate, a drug holiday of approximately 6 months is insufficient to recover osteoclast activity.